Serous Borderline Tumor in Transgender Female-to-Male Individuals: A Case Report of Androgen Receptor-Positive Ovarian Cancer - Cristina Ferreira; João Fraga; Célia Antunes; Manuela Gonçalo; Paulo Donato (Case Reports in Radiology)
Ovarian cancer is the most fatal gynecologic malignancy. The incidence of ovarian cancer among female-to-male transsexuals receiving treatment with testosterone is unknown, and few cases have been reported in the literature. We report a recent case in our institution, a 23-year-old female-to-male transsexual patient who received testosterone supplementation. The patient underwent a pelvic magnetic resonance imaging to study an ovarian complex cyst that revealed the presence of a bilateral ovarian tumor with imaging features of borderline serous tumor. These masses were surgically removed and the pathology report confirmed the diagnosis associated with noninvasive peritoneal implants and the presence of numerous androgen receptors in the tumor cells. Although there is still insufficient data to validate a direct correlation between hormonotherapy and ovarian cancer in these patients, this case may reinforce previous reports on this association and highlights the relevance of radiological follow-up and bilateral salpingo-oophorectomy as part of gender reassignment surgery.